Desigualdad, instituciones y crecimiento económico en América Latina - Coatsworth, John H. (2012)
Inequality, institutions and economic growth in Latin AmericaThis essay examines three recent historical approaches to the political economy of Latin America’s relative economic backwardness. All three locate the origins of contemporary underdevelopment in defective colonial institutions linked to inequality. The contrasting view offered here affirms the significance of institutional constraints, but argues that they did not arise from colonial inequalities, but from the adaptation of Iberian practices to the American colonies under conditions of imperial weakness. Colonial inequality varied across the Americas; while it was not correlated with colonial economic performance, it mattered because it determined the extent of elite resistance to institutional modernization after independence. The onset of economic growth in the mid to late nineteenth century brought economic elites to political power, but excluding majorities as inequality increased restrained the region’s twentieth-century growth rates and prevented convergence